Evaluating the Strength of the Friction Stir Welded Joints at Various Rotational Speeds - Varma, Ramaraju Ramgopal; Abdullah, Ibrahim; Reddy, Baridula Ravinder (scientific.net, 2014)
The present research paper aims in evaluating the strength of the welded AA6351 alloy plates of 6 mm thick by using friction stir welding technique at different rotational speeds The applied welding technique is capable of achieving the mechanical properties of the alloy close to that of the original alloy. In the present investigation, the speeds of the spindle were varied from 1100 rpm to 1500 rpm with a constant transverse speed of 20 mm/min. The tensile strength of the joints is determined by an universal testing machine. The results from the present investigation show that the values of the yield strength were very much closer to the values of the AA6351Alloy prior to welding. It has been found from the experiments that the strength of the joints increases with the increase in the rotational speed; however, the same is decreasing after achieving certain speed.